Evidence of Hermaphroditism and Sex Ratio Distortion in the Fungal Feeding Nematode Bursaphelenchus okinawaensis - Shinya, Ryoji (Genetics Society of America, 2014)
Nematodes have many different reproductive strategies along with their divergent life histories; the ability of hermaphrodite to self- and cross-fertilize is useful for genetic manipulation. Here, we demonstrate the hermaphroditism of the fungal feeding nematode Bursaphelenchus okinawaensis, which was formerly described as a parthenogenetic nematode, and we show its other unique sexual characteristics. To determine that it is hermaphroditic, we performed the following experiments: observation of the pronuclear and chromosome behavior during oogenesis and early embryogenesis; observation of spermatogenesis during the fourth larval stage; investigation of sperm utilization; and investigation of phenotypic segregation after cross-mating using a chemically induced visible mutant. We then investigated the mating preferences and spermatid size difference between males and hermaphrodites. B. okinawaensis males successfully mated only with sperm-depleted old hermaphrodites, and the spermatid sizes of males were almost the same as those of hermaphrodites. Moreover, the sex ratio of cross-fertilized progeny was highly skewed toward hermaphrodites. B. okinawaensis is phylogenetically distant from established model nematodes such as C. elegans and is more closely related to some economically relevant parasitic nematodes. This newly discovered hermaphroditic nematode has great potential for evolutionary and parasitological research.